Função reflexiva e capacidade de mentalização em pais de crianças em cuidados paliativos - Paiani, Raquel Lacerda (Universidade do Vale do Rio dos Sinos, 2024)
A good mentalization (M) and reflective functioning (RF) can serve as a protective factor in situations of stress and trauma, particularly within the context of palliative care (PC). The objective was to understand the experience of parents of children in palliative care from the perspective of the mentalization approach. This is a qualitative, exploratory, cross-sectional study comprising multiple case studies conducted in a hospital in the capital of Rio Grande do Sul. The participants included 5 fathers, 3 mothers and 2 fathers of children who were being monitored by the PC team. The children were between the ages of 16 days and 7 years. The diagnoses were a genetic anomaly and other oncological diagnoses of a head tumor. The Sociodemographic and Clinical Data Questionnaire, the Reflective Functioning Questionnaire and the Life History and Current Relationships Interview were employed for data collection. The findings indicate that parents with good M are more equipped to navigate the emotional complexities associated with their child's diagnosis and treatment. These competencies enable parents to more effectively regulate and interpret their own emotional states, which in turn facilitates more appropriate emotional support for their children.
Keywords: Cuidados paliativos; Crianças; Pais; Capacidade de mentalização; Função reflexiva; Palliative care; Children; Parents; Mentalization; Reflective functioning; ACCNPQ::Ciências Humanas::Psicologia